Dynamic, transient, and robust increase in the innervation of the inflamed mucosa in inflammatory bowel diseases - Gonzalez Acera, Miguel; Bubeck, Marvin; Mascia, Fabrizio; Diemand, Leonard; Sturm, Gregor; Kuehl, Anja A.; Atreya, Raja; Lie, Dieter Chichung; Neurath, Markus; Schumann, Michael; Klose, Christoph S. N.; Trajanoski, Zlatko; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are characterized by chronic dysregulation of immune homeostasis, epithelial demise, immune cell activation, and microbial translocation. Each of these processes leads to proinflammatory changes via the release of cytokines, damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns (PAMPs), respectively. The impact of these noxious agents on the survival and function of the enteric nervous system (ENS) is poorly understood. Here, we show that in contrast to an expected decrease, experimental as well as clinical colitis causes an increase in the transcript levels of enteric neuronal and glial genes. Immunostaining revealed an elevated neuronal innervation of the inflamed regions of the gut mucosa. The increase was seen in models with overt damage to epithelial cells and models of T cell-induced colitis. Transcriptomic data from treatment naïve pediatric IBD patients also confirmed the increase in the neuroglial genes and were replicated on an independent adult IBD dataset. This induction in the neuroglial genes was transient as levels returned to normal upon the induction of remission in both mouse models as well as colitis patients. Our data highlight the dynamic and robust nature of the enteric nervous system in colitis and open novel questions on its regulation.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Crohn’s disease; Enteric nervous system; Inflammatory bowel diseases; Neurogenesis; Ulcerative colitis

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Guardians of the gut: influence of the enteric nervous system on the intestinal epithelial barrier - Bubeck, Marvin; Becker, Christoph; Patankar, Jay (Frontiers in Medicine, 2023)
The intestinal mucosal surface forms one of the largest areas of the body, which is in direct contact with the environment. Co-ordinated sensory functions of immune, epithelial, and neuronal cells ensure the timely detection of noxious queues and potential pathogens and elicit proportional responses to mitigate the threats and maintain homeostasis. Such tuning and maintenance of the epithelial barrier is constantly ongoing during homeostasis and its derangement can become a gateway for systemic consequences. Although efforts in understanding the gatekeeping functions of immune cells have led the way, increasing number of studies point to a crucial role of the enteric nervous system in fine-tuning and maintaining this delicate homeostasis. The identification of immune regulatory functions of enteric neuropeptides and glial-derived factors is still in its infancy, but has already yielded several intriguing insights into their important contribution to the tight control of the mucosal barrier. In this review, we will first introduce the reader to the current understanding of the architecture of the enteric nervous system and the epithelial barrier. Next, we discuss the key discoveries and cellular pathways and mediators that have emerged as links between the enteric nervous, immune, and epithelial systems and how their coordinated actions defend against intestinal infectious and inflammatory diseases. Through this review, the readers will gain a sound understanding of the current neuro-immune-epithelial mechanisms ensuring intestinal barrier integrity and maintenance of intestinal homeostasis.
CRIS-Team Scopus Importer:2023-09-15
Keywords: enteric glia; enteric nervous system; gut epithelial barrier; inflammatory bowel disease; intrinsic primary afferent neurons

Myenteric Plexus Immune Cell Infiltrations and Neurotransmitter Expression in Crohn’s Disease and Ulcerative Colitis - Wiese, Jakob J.; Manna, Subhakankha; Kühl, Anja A.; Fascì, Alberto; Elezkurtaj, Sefer; Sonnenberg, Elena; Bubeck, Marvin; Atreya, Raja; Becker, Christoph; Weixler, Benjamin; Siegmund, Britta; Patankar, Jay; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Pain is a cardinal symptom in inflammatory bowel disease [IBD]. An important structure in the transduction of pain signalling is the myenteric plexus [MP]. Nevertheless, IBD-associated infiltration of the MP by immune cells lacks in-depth characterisation. Herein, we decipher intra- and periganglionic immune cell infiltrations in Crohn´s disease [CD] and ulcerative colitis [UC] and provide a comparison with murine models of colitis. Methods: Full wall specimens of surgical colon resections served to examine immune cell populations by either conventional immunohistochemistry or immunofluorescence followed by either bright field or confocal microscopy. Results were compared with equivalent examinations in various murine models of intestinal inflammation. Results: Whereas the MP morphology was not significantly altered in IBD, we identified intraganglionic IBD-specific B cell- and monocyte-dominant cell infiltrations in CD. In contrast, UC-MPs were infiltrated by CD8+ T cells and revealed a higher extent of ganglionic cell apoptosis. With regard to the murine models of intestinal inflammation, the chronic dextran sulphate sodium [DSS]-induced colitis model reflected CD [and to a lesser extent UC] best, as it also showed increased monocytic infiltration as well as a modest B cell and CD8+ T cell infiltration. Conclusions: In CD, MPs were infiltrated by B cells and monocytes. In UC, mostly CD8+ cytotoxic T cells were found. The chronic DSS-induced colitis in the mouse model reflected best the MP-immune cell infiltrations representative for IBD.
CRIS-Team Scopus Importer:2024-02-16
Keywords: abdominal pain; Enteric nervous system; IBD; immune cell infiltration; inflammatory bowel disease; myenteric plexus; submucosal plexus; visceral pain